Develop Model Harmonization ATFM and A-CDM with Integrated Policy Network Supporting Air Traffic Services - Fitrianti, Rachma; Malkhamah, Siti; Djunaedi, Achmad; Dewanti, Dewanti (Ridwan Institute, 2024)
This study presents an illustration of the Development of the Integrated Policy Network Model Harmonization of ATFM and A-CDM based on Higher Order Thinking Skills to find out how digital transformation in the innovation of ATM System implementation in Indonesia. This research is included in Soft System Methodolgy with the category of theoretical research practice or research interest. According to Checkland and Scholes (1990) and Checkland (1989) is a reflection on problem situations in the real world based on a certain methodology and intellectual framework. The results of the study are expected to show that the Development of the Integrated Policy Network Model Harmonization of ATFM and A-CDM is also determined by the HOTS (Higher Order Thinking Skills) of aviation personnel on the three main capabilities needed for the future, namely: analytical, critical, and creative. Personnel are expected to be able to recognize the complexities and possible problems that exist in the provision of aviation services to support Decision Making. And it is expected to be an input for the government and the highest leadership of an aviation industry as policy makers, in order to improve the Development of the ATFM and A-CDM-based Harmonization Network Integrated Policy Model HOTS. As a result of the HOTS study, according to Checkland & Scholes (1990), the Integrated Policy Network Model of Atfm and A-CDM Harmonization is an experience-based knowledge from HOTS based on the innovation of the application of the ATM System to influence the improvement of aviation personnel as the use of facilities and individuals in the organization through the Design Approach Soft System Methodolgy.